Desempenho energético e operacional do conjunto trator-semeadora em função de coberturas do solo e mecanismos sulcadores: atributos físicos do solo e componentes de produtividade - Nicolau, Francisca Edcarla de Araujo (2016)
The mechanisms of furrow openers seeder exert importance in tratório and energy performance of tractor- seeder set . The objective of this study was to estimate energy and operational demand of tractor-seeder set associated to corn sowing, soil physical properties and productivity components depending on soil covers and furrower mecanisms in Northeast Region of Brazil. The experiment was installed at the Federal University of Ceará, Fortaleza, Ceará, in an Yellow Red Argisol. The experiment was set in a randomized block design, in a (2x3) +2 factorial scheme, with four replicates resulting in 32 experimental plots. The treatments were two furrower mecanisms (disc furrower and shank) and three cover crops (sunn hemp, sorghum and mombasa grass) and two controls (maize on bare soil traeted with disc furrower and with shank). Power and operational performance of tractor-seeder set, soil physical attributes and maize phytotechnical characteristics were evaluated. The soil total porosity showed no significance to the mechanisms and to the soil covers in three depths analyzed. This result is associated with no difference of soil macro and microporosity of treatments, because the total porosity is obtained by the sum of macro and soil microporosity. The shank showed higher specific operational resistance that was obtained by force per mobilized area, due to the shank require more force to pull seeder and the statistical equivalence of mobilized area. Plant height and first ear height were evaluated because these genetic caracteristics could be influenced by production system, and the results presented cover crops, especially sunn hemp, provided the growth of maize. The disc furrower required greater energy demand on specific consumption and specific consumption per mobilized area and resulted better operational performance of tractor-seeder set (less slippage of the front and rear axles and greater travel speed). Sunn hemp cover provided lower density of soil at depths of 0.0 to 0.10 m and 0.20 to 0.30 m and presented the highest corn productivity.